Strategi Manajemen Konflik dalam Pengembangan Soft Skill dan Hard Skill Siswa Kelas 7 SMP Science Qur’an Al-Irsyad Jember - Maharani, Nur Silvia; Anisa, Oktaviana Dwi; Mayangsari, Rika Ifana Putri; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2022)
This study aims to explain how conflict management strategies affect the development of soft skills and hard skills for grade seven students at SMP Science Qur'an Al-Irsyad Jember. This study used a qualitative approach with case study design. Data and data sources in this study were obtained from interviews with student teachers and six students. In addition, data were also obtained from observations and documentation studies. The results of the study show that the conflicts that impede the ability of students' soft skills and hard skills are lazy to study, bored in learning, differences in IQ, lazy to read and write, and lazy to participate in other mandatory activities. As for the several efforts that have been made to resolve conflicts and to develop hard skills and soft skills, SMP Science Qur'an Al-Irsyad educational institutions have their own strategies. Conflict management strategies in developing soft skills use classroom development methods such as tutoring, public speaking exercises such as speeches and becoming Uswatun Hasanah, while conflict management strategies in developing hard skills, use additional hour methods such as extra curricular archery, coding (IT), writing scientific, scout, and tahfidzul qur'an.